2000
DOI: 10.1046/j.1423-0410.2000.7840209.x
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Inactivation of Bacteria and HIV in Buffy‐Coat‐Derived Platelet Concentrates under Conditions That Preserve in vitro Platelet Function

Abstract: PCT with 150 microM S-59 and a 3 J/cm(2) UVA treatment does not adversely affect in vitro properties of BC PCs stored at 22 degrees C for 7 days. The PCT process inactivated bacteria and HIV-1 inoculated into the BC PCs. These results extend the earlier reported efficacy of PCT apheresis PCs to BC PCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
1
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 22 publications
9
90
1
1
Order By: Relevance
“…31 Previously reported studies have demonstrated that the PCT technology provides robust inactivation of viruses, bacteria, and leukocytes in platelet components. 5,8,9 Based on this clinical trial, pooled platelet components prepared with PCT and stored for up to 5 days offer the potential to reduce transfusion-associated infections and inactivate residual contaminating leukocytes using a processing system that is compatible with the current method of preparing therapeutic doses of buffy coat platelets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Previously reported studies have demonstrated that the PCT technology provides robust inactivation of viruses, bacteria, and leukocytes in platelet components. 5,8,9 Based on this clinical trial, pooled platelet components prepared with PCT and stored for up to 5 days offer the potential to reduce transfusion-associated infections and inactivate residual contaminating leukocytes using a processing system that is compatible with the current method of preparing therapeutic doses of buffy coat platelets.…”
Section: Discussionmentioning
confidence: 99%
“…11 Pooled platelet concentrates were leukoreduced by filtration followed by photochemical treatment (PCT) with 150 M S-59 and 3 J/cm 2 UVA treatment (Helinx Technology; Cerus Corporation, Concord, CA) for pathogen and leukocyte inactivation. 5,8,9 After PCT, pooled platelet concentrates were stored for up to 5 days before transfusion. PCT was used in place of ␥ irradiation for prevention of transfusion-associated graft-versus-host disease.…”
Section: Platelet Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing the risk even further may ultimately require alternative approaches, such as pathogen reduction. 15,[18][19][20] While the current culture systems have increased platelet safety, there are a number of costs: higher prices for platelets, 1-2% product loss from sampling and 12-30 hour delays in platelet product release, potentially affecting platelet availability. 21 It is hoped that these costs will be offset by the benefits of being able to extend platelet storage beyond the 5-day limit.…”
Section: Impact Of Bacterial Testingmentioning
confidence: 99%
“…Starting in 1989, a series of research publications examined the utility of existing psoralens (8-MOP and AMT) and novel psoralens (amotosalen HCl) for the inactivation of infectious pathogens and leukocytes in platelet and plasma blood components. [27][28][29][30][31][32][33][34][35][36] Recently, a photochemical process using amotosalen HCl has received European approval for inactivation of infectious pathogens and leukocytes in platelet components. 37 This technology utilizes the novel psoralen compound amotosalen HCl, formerly known as S-59, and long wavelength ultraviolet light (UVA) to induce the formation of irreversible, covalent psoralen-nucleic acid adducts ( Figure 2).…”
Section: Risk Factors For Ta-gvhd and Current Technologymentioning
confidence: 99%